Penguatan Kemandirian Ekonomi Masyarakat Berbasis Potensi Limbah Sabut Kelapa di Desa Tolongio - Ariawan, Ariawan; Syamsir, Syamsir; Hulukati, Stephan Adriansyah; Ngabito, Fatmah. M (Penerbit Goodwood, 2025)
Purpose: The plantation sector is a potential sector spread across North Gorontalo Regency very widely. The commodity with potential is coconut with total production in 2021 of 9,329.73 tons. The amount of coconut production per year is 9,329.73 tons, producing coconut fiber waste. With the calculation that each ton of coconut produces 35% -40%, 3731.90 tons of coconut fiber waste is produced. Methodology: Based on this background, several activity methods were designed as a way out of the problem in question. First, socialization was carried out regarding the potential possessed by Tolongio village, Anggrek District, North Gorontalo Regency. Followed by 50 participants consisting of Bumdes Nusa Indah administrators, Helumo youth organization, village officials, students, and the community. Second, training in making products from coconut fiber waste, Third, assistance in making products and establishing business units for sustainability Results: Evaluation carried out to measure the level of the achievements of the activities that have been carried out, increasing skills in making community products increased by 81%, partners' understanding and knowledge regarding the use of coconut fiber waste increased by 87%, understanding of partners' business management increased by 83%. Conclusion: The result of the mentoring activities is the formation of a new business unit ready to produce cocopeat, cocofiber, and cocobristle under the name Nusa Kelapa with SK number; 800/DT-Angg/19/X/2023. Limitation: This activity is limited to processing coconut fiber waste in Tolongio village by utilizing technology and establishing a business unit as a management institution. Contribution: The contribution given to activity partners is in the form of making and handing over coconut fiber waste processing equipment into fibers with export value, in addition to several empowerment activities and the formation of business units managed by village youth.